Work Stress, Transformational Leadership, and Employees’ Psychological Well-Being: Evidence from PT X Bandung - Qansha Ramaniya Ailsa; Pras Rendy; Recky Recky; Kartika Nuradina (International Journal of Marketing & Human Resource Research, 2026)
This study examines the relationships between work stress, transformational leadership, and employees’ psychological well-being at PT X Bandung. A quantitative explanatory design was employed using a cross-sectional survey. The study involved all 65 active employees, who were selected through total sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed with descriptive statistics, item validity testing, reliability testing, regression diagnostics, and multiple linear regression using IBM SPSS Statistics version 26. The results showed that work stress had a negative but statistically nonsignificant association with psychological well-being (B = −0.063, t = −0.355, p = 0.724). This finding indicates that the available data did not provide sufficient evidence that work stress independently predicted psychological well-being after transformational leadership was controlled. In contrast, transformational leadership had a positive and statistically significant association with psychological well-being (B = 0.814, t = 4.273, p < 0.001). The overall regression model was significant, F(2, 62) = 22.644, p < 0.001, and explained 42.2% of the variance in psychological well-being, with an adjusted R² of 0.403. These findings suggest that transformational leadership is an important organizational factor associated with employees’ psychological well-being. However, the results should be interpreted cautiously because the study used a cross-sectional design, involved a single organization, and identified non-normal regression residuals